PENGARUH BIOLARVASIDA BERBAGAI BIJI TANAMAN KHAS INDONESIA SEBAGAI KONTROL VEKTOR NYAMUK AEDES AEGYPTI DALAM PENELITIAN EKSPERIMENTAL : Literature Review - Rizqi Fawazullah (2022)
Indonesia is an endemic country for Dengue Hemorrhagic Fever (DHF) with the vector of transmission through the bite of the Aedes aegypti mosquito. In 2020 in Indonesia there were 95,893 cases of DHF with a death rate of 661 people. Currently the prevention of DHF is done by using chemical larvicides, namely abate, but it can cause resistance. So we need natural ingredients that have the ability as larvicides, the part of the plant that has larvicidal activity but is still rarely used is plant seeds. This study aims to determine the effectiveness of typical Indonesian plant seeds as natural larvicides against Aedes aegypti. The method used in this study was Literature Review and took articles and journals from Google Scholar and PubMed data centers with the keywords 'plant seed efficacy test against Aedes aegypti larvae' and 'Plant seed bio larvacide against Aedes aegypti larvae'. There were 1510 articles and journals that matched the keywords and then 1497 articles and journals were excluded due to discrepancies in the title, abstract, and the unavailability full text of the article. There were 13 articles and journals that entered the inclusion criteria and a Literature Reviewon the 13 articles and journals. The results were assessed from the smallest LC 50, which was 6.25242 ppm for the sugar apple seed extract, while the largest LC 50 was 47580 ppm for the mango seed extract.